Development of an Enhanced Anti-Aging Formulation - Vikas Kumar Singh , Reenu Yadav , Sanjay Kumar , Phool Singh Yaduvanshi , Gaurav Jain , Kavita R Loksh (Cuestiones de Fisioterapia, 2025)
This study investigates the anti-aging and antimicrobial properties of fresh blueberry and banana fruits. It begins with phytochemical screening and identification of active compounds in the extracts, providing a foundation for understanding their therapeutic effects. The extracts were evaluated for physical properties, antioxidant, and antiaging activities, leading to the development of an anti-aging herbal transdermal gel.